2021
DOI: 10.1186/s12894-020-00778-0
|View full text |Cite
|
Sign up to set email alerts
|

The distribution pattern of periprostatic neurovascular bundles examined with successive celloidin slices

Abstract: Background Although several distribution patterns of periprostatic neurovascular bundles have been proposed, variant dissection technique based on these patterns still confused surgeons. The aim of this study was to describe the periprostatic neurovascular bundles and their relationship with the fascicles around prostate and provide the accurate morphologic knowledge of periprostatic tissue for prostate operation. Methods The pelvic viscera were ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It is noteworthy that the periprostatic fascia cannot be identified as a single-layer stretching over the lateral surface of the prostate. It contains much more in the majority of cases, both collagenous and adipose tissue elements, and depicts as a multi-layered structure ( 2 , 19 ). The periprostatic fascia may be subdivided into three sections according to the anatomical locations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that the periprostatic fascia cannot be identified as a single-layer stretching over the lateral surface of the prostate. It contains much more in the majority of cases, both collagenous and adipose tissue elements, and depicts as a multi-layered structure ( 2 , 19 ). The periprostatic fascia may be subdivided into three sections according to the anatomical locations.…”
Section: Resultsmentioning
confidence: 99%
“…The observed space consisted of loose connective and adipose tissue referred to as areolar tissue ( 24 ). Li et al reported in a small case series of human cadaveric studies that on the most convex region of the lateral prostate, both the lateral periprostatic fascia and the pseudocapsule are highly like to fuse into one structure temporarily ( 19 ). The authors furthermore highlighted the necessity of performing a careful fascia-pseudocapsule separation in order to the minimize damage to surrounding structures ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The visceral endopelvic fascia, a structure covering the anterior surface of the prostate, fuses with the anterior fibromuscular stroma in the midline to form a pouch-like complex that envelops the prostate and urethra ( 19 , 20 ). The Pubic prostatic ligament complex is also closely associated with urinary control and erectile function ( 21 ). The puboprostatic ligament anchors the bladder, prostate and membranous urethra at the pubic symphysis; The the fascial tendinous arch of pelvis is a fused portion of the mural and visceral components of the intrapelvic fascia that extends from the puboprostatic ligament to the sciatic spine; the puboperinealis muscle is a paired muscle of pubic bone origin located at the prostate-urethral junction and terminating most at the perineal body, which acts as a “hammock “ and supports the urethra posteriorly and is responsible for the cessation of urination ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%